Enhancement of honey encryption algorithm applied in thinkgeek online shopping - Joash Gianne T. Paras and Mary Joise Ann Z. Caliwag. 4 0 16; 5 (2019)
u
Undergraduate Thesis: (BSCS major in Computer Science) -Pamantasan ng Lungsod ng Maynila, 2019.
Keywords: 2 -- 0; 6; 20; 20; 2